An Insight into Teachers' Classroom Practices: The Case of Secondary Education Science Teachers - Angelos Sofianidis; Maria Kallery (MDPI AG, 2021)
Teachers' knowledge rooted in classroom practices guides their actions when dealing with a specific subject matter. To assess the quality of these practices, a close examination of the "classroom reality" is needed. The present study, which was carried out in Greece, investigates secondary science teachers' practices. To record these practices, we used special classroom observation tools as well as questionnaires to record students' views of their teachers' practices. The observation tools and the student questionnaire focus on specifically formed criteria deriving from aspects of Pedagogical Content Knowledge (PCK). In total, 32 secondary science teachers and 1154 students participated in our study. The results indicated that the strong points of teachers' teaching practices concern their subject matter knowledge, the use of representations, their questioning, their communication of the instructional objectives to the students, and knowledge of students' difficulties. The weak points are related to the use of a variety of teaching approaches, the investigation of the students' alternative conceptions, the experimental and ICT-based teaching, and the implementation of inquiry-based activities. The methodology employed in our study was fruitful in providing a holistic view of science teachers' practices and can be used for investigating classroom practices of teachers of other subjects as well.